COVID-19: Social Distancing and Physical Activity in United Kingdom Residents With Visual Impairments. (November 2022) - Strongman, Clare; Swain, Patrick; Chung, Henry; Merzbach, Viviane; Gordon, Dan
Introduction: The introduction of the COVID-19 lockdown and social distancing policy has the potential to restrict access to physical activity, change exercise behavior, and to increase sedentary behavior. This study was conducted with the support of British Blind Sport and evaluates the effect of the lockdown policy on adults with visual impairments in the United Kingdom (UK).Methods: An online survey based on the World Health Organization's Global Physical Activity Questionnaire was completed by 73 participants (median age 35–44 years, 59% female) to gain information on how the implementation of the lockdown policy by the UK government has affected physical activity and sedentary behavior in adults that are visually impaired. Paired sample t-tests and Wilcoxon signed rank tests were used to analyze continuous and Likert scale data, respectively.Results: The majority of participants continued to exercise during lockdown, but the nature of this activity altered with a significant change to exercising in a private indoor space (+190% (always), z = −3.871, p < 0.001), and those exercising alone (+118% (always), z = −2.595, p = 0.009). The volume of activity reduced in all cases, between −11% and −52%, with significant changes in duration of vigorous day-to-day activity, moderate day-to-day activity, travel by foot or cycle, and vigorous recreational activity. Sedentary behavior increased on average by 21% ( t (59) = −2.050, p = 0.045), with a greater effect seen in females (+36%, t (35) = −2.525, p = 0.016).Discussion: Reductions in physical activity volume and increases in sedentary behavior are consequences of the UK lockdown for those with visual impairments. The health and well-being implications of these data to this specific population are of particular concern.Implications for Practitioners: Lockdown measures should be designed with consideration of the needs of people with disabilities. Innovative ways to engage these populations in physical activity are strongly encouraged.